2019
DOI: 10.1139/cjas-2018-0031
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional recommendations and management practices adopted by feedlot cattle nutritionists: the 2016 Brazilian survey

Abstract: The feedlot industry in Brazil is still evolving, and some nutritional management recommendations adopted by nutritionists changes from year to year. The main objective of this survey was to provide a snapshot of current nutritional management practices adopted in Brazilian feedlots. The 33 nutritionists surveyed were responsible for approximately 4 228 254 animals. Corn remained as the primary source of grain used in feedlot diets by the participants, whereas fine grinding was the primary grain processing met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
74
2
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 12 publications
13
74
2
13
Order By: Relevance
“…During this period, the bull calf is required to transition from a forage-based diet to a high-concentrate diet. In general, the average adaptation period in Brazilian feedlots is reported to be 16.2 days ( Pinto and Millen, 2018 ). Further work evaluating different adaptation periods ( Perdigão et al, 2017 ; Barducci et al, 2019 ; Parra et al, 2019 ) suggested that Nellore cattle should spend a minimum of 14 days adapting to a high-concentrate diet in a step-up manner, where increasing amounts of concentrate are successively added to the adaptation diet.…”
Section: Introductionmentioning
confidence: 99%
“…During this period, the bull calf is required to transition from a forage-based diet to a high-concentrate diet. In general, the average adaptation period in Brazilian feedlots is reported to be 16.2 days ( Pinto and Millen, 2018 ). Further work evaluating different adaptation periods ( Perdigão et al, 2017 ; Barducci et al, 2019 ; Parra et al, 2019 ) suggested that Nellore cattle should spend a minimum of 14 days adapting to a high-concentrate diet in a step-up manner, where increasing amounts of concentrate are successively added to the adaptation diet.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, cereal grains represent more than 51% of feedlot diets composition [1,2], with corn and sorghum being the most used grains in those diets [3]. However, grain price volatility and metabolic disorders accompany the use of high grain levels in beef cattle diets.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, feedlot diets that usually contain increased amounts of energy due to high levels of concentrate inclusion [18] can cause excessive fermentation in the cecum, thereby contributing to the metabolizable energy of ruminants [19,20], however, it may generate inflammatory reactions in the cecal epithelium. Feed additives that are able to increase the use of starch in the rumen, reducing the escape of starch to the intestines, as well as lower starch levels in the diet of feedlot cattle, can avoid the risk of cecal acidification.…”
Section: Introductionmentioning
confidence: 99%